Adjuvanticity of β -Glucan for Vaccine Against Trichinella spiralis - Liu, Yi; Liu, Xiaolei; Yang, Li; Qiu, Yangyuan; Pang, Jianda; Hu, Xiaoxiang; Dong, Zijian; Liu, Zengshan; Jin, Xuemin (Frontiers in Cell and Developmental Biology, 2021)
In the past 30 years, few researches focus on the protective immunity of adjuvant against T. spiralis infection. There is an urgent need to develop new, improved vaccine adjuvants for T. spiralis infection. It has been reported that polysaccharides are effective, safe, and biodegradable as adjuvant for infectious diseases. In this paper, we first observed the adjuvanticity of β-glucan as adjuvant for defensing helminth T. spiralis in vivo. We showed that IgG and IgE were elevated in the mice immunized with β-glucan combined with recombinant T. spiralis serine protease inhibitor (rTs-Serpin), which is one of the vaccine candidates. Furthermore, in vitro, the combination of β-glucan and rTs-Serpin enhanced the maturation of bone marrow dendritic cells (BMDCs) compared to rTs-Serpin alone.We showed that β-glucan + rTs-Serpin –treated BMDCs secreted higher production of IL-12 and IL-10. Moreover, β-glucan + rTs-Serpin –treated BMDCs not only promoted the population of CD4+ IFN-γ+ T cells, but also enhanced the population of CD4+ IL-4+ T cells. These findings suggested that β-glucan, as an adjuvant, have the capacity to protect against T.spiralis infection via activating both Th1 and Th2 immune response.